Herbal-induced Stevens-Johnson syndrome with oral involvement and management in an HIV patient - S. Suniti; Irna Sufiawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Stevens-Johnson syndrome (SJS) is an immune complex-mediated hypersensitivity reaction affecting the skin and mucous membranes. Patients infected with human immunodeficiency virus (HIV) are at increased risk of developing SJS which is predominantly caused by an adverse reaction to medications, including herbal varieties. In recent years, the consumption of herbal medicines has increased, while their safety remains a matter for investigation. Purpose: The purpose of this case report is to explain the occurrence of SJS caused by herbal medicine. Case: A 43-year-old male patient with body-wide skin erosion was referred to the Department of Oral Medicine and subsequently diagnosed with Stevens-Johnson syndrome due to his consumption of a herbal medicine containing zingiber rhizoma, coboti rhizoma, asari herbal and epimedi. The patient’s chief complaints included difficulty when opening the mouth, dysphagia and excessive production of saliva continuously contaminated with blood and sputum. Extraoral examination showed a sanguinolenta crust on the lips. Intra oral examination of oral mucous showed erosive lesions with bleeding and pain. A HIV test performed at a Clinical Pathology Laboratory was positive for antibodies against HIV with a CD4 cell count of 11 cells/ml. Case management: Treatment consisted of the administering of NaCl 0.9 %, hydrocortisone 0.1% and Chlorhexidine digluconate 0.12% for 12 days. Conclusion: SJS can be caused by herbal medicine and it is essential to be aware of the latter’s potential adverse effects, especially in immunocompromised patients. Symptomatic management of oral lesions should be planned as an early intervention in order to decrease morbidity and mortality in SJS patients.